Revealing sub‐voxel motions of brain tissue using phase‐based amplified MRI (aMRI). Issue 6 (30th May 2018) - Terem, Itamar; Ni, Wendy W.; Goubran, Maged; Rahimi, Mahdi Salmani; Zaharchuk, Greg; Yeom, Kristen W.; Moseley, Michael E.; Kurt, Mehmet; Holdsworth, Samantha J.
Abstract : Purpose: Amplified magnetic resonance imaging (aMRI) was recently introduced as a new brain motion detection and visualization method. The original aMRI approach used a video‐processing algorithm, Eulerian video magnification (EVM), to amplify cardio‐ballistic motion in retrospectively cardiac‐gated MRI data. Here, we strive to improve aMRI by incorporating a phase‐based motion amplification algorithm. Methods: Phase‐based aMRI was developed and tested for correct implementation and ability to amplify sub‐voxel motions using digital phantom simulations. The image quality of phase‐based aMRI was compared with EVM‐based aMRI in healthy volunteers at 3T, and its amplified motion characteristics were compared with phase‐contrast MRI. Data were also acquired on a patient with Chiari I malformation, and qualitative displacement maps were produced using free form deformation (FFD) of the aMRI output. Results: Phantom simulations showed that phase‐based aMRI has a linear dependence of amplified displacement on true displacement. Amplification was independent of temporal frequency, varying phantom intensity, Rician noise, and partial volume effect. Phase‐based aMRI supported larger amplification factors than EVM‐based aMRI and was less sensitive to noise and artifacts. Abnormal biomechanics were seen on FFD maps of the Chiari I malformation patient. Conclusion: Phase‐based aMRI might be used in the future for quantitative analysis of minute changes in brain motion and may reveal subtle physiological variations of the brain as a result of pathology using processing of the fundamental harmonic or by selectively varying temporal harmonics. Preliminary data shows the potential of phase‐based aMRI to qualitatively assess abnormal biomechanics in Chiari I malformation.